Chinese Herbal Medicine, Guilu Erxian Glue, as Alternative Medicine for Adverse Side Effects of Chemotherapy in Doxorubicin-Treated Cell and Mouse Models. (5th April 2021) - Lien, Chia-Ying; Lu, Chen-Wen; Lin, Yi-Hsuan; Wu, Wan-Jhen; Hsu, Chih-Hsiang; Chuang, Tai-Yuan; Lin, Kuei-Fu; Chuang, Wu-Chang; Lee, Ming-Chung; Wu, Chung-Hsin
Abstract : Doxorubicin (DOX), a chemotherapeutic drug, often causes many adverse side effects in patients with cancer, such as weight loss, motor disability, blood circulation defects, myelosuppression, myocardial injury, joint degeneration, and bone loss. The Chinese herbal medicine Guilu Erxian Glue (GEG) has been used in the prevention and treatment of osteoarthritis and osteoporosis for hundreds of years, with considerably fewer side effects. We expected that GEG could serve as a protective and beneficial alternative treatment for DOX-induced adverse side effects. In this study, we evaluated whether GEG can alleviate DOX-induced weight loss, motor disability, abnormal blood circulation, myelosuppression, myocardial injury, joint degeneration, and bone loss by using chemotherapy models of synoviocyte cell line HIG-82 and mice. Moreover, we examined the antioxidant capacity of GEG by using DPPH (1, 1-diphenyl-2-picrylhydrazyl) free-radical scavenging. Our results revealed that GEG treatment can significantly enhance DPPH free-radical scavenging and reduce DOX-induced cytotoxicity in synoviocyte HIG-82 cells. In addition, GEG treatment for 2 weeks can significantly relieve weight loss, enhance exhaustive exercise capacity, improve blood circulation, alleviate myocardial oxidative stress and inflammation, and strengthen the tibias of DOX-treated mice. Thus, we suggest that GEG treatment can be a protective and alternative therapy for alleviating chemotherapy-related side effects such as weight loss, motor disability, blood circulation defects, and bone loss.